Factors Influencing The Utilization of Antenatal Care (K4) in Pregnant Women at The Pondok Meja Community Health Center, Muaro Jambi Regency in 2024 - Br Tarigan Tua, Pratenta; Sari, Rumita Ena; Hubaybah, Hubaybah; Wardiah, Rizalia; Ibnu, Ismi Nurwaqiah (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Antenatal care is a service provided to pregnant women, including physical and psychological health monitoring, fetal growth and development assessment, and preparation for labor and delivery. According to data from the World Health Organization (WHO), an estimated 500 women die each day due to complications related to pregnancy and childbirth. A decrease in the utilization of antenatal care visits has been observed at the Pondok Meja Health Center. Therefore, this study aims to identify the factors associated with the utilization of antenatal care at the Pondok Meja Health Center. This study employed a quantitative method with a cross-sectional design, using univariate, bivariate, and multivariate data analyses. The research sample consisted of mothers with children under six months of age within the working area of the Pondok Meja Health Center between September 2024 and January 2025. A total of 145 respondents were selected using a stratified sampling method. Several variables were found to be significantly associated with the utilization of antenatal care services, including employment status (p = 0.003) and health workers (p = 0.002). Meanwhile, variables not significantly associated included age (p = 0.128), parity (p = 0.392), education level (p = 1.000), knowledge (p = 0.127), family support (p = 0.496), disease history (p = 0.896), and satisfaction level (p = 0.070). The most influential factor was employment status (PR = 3.276). Both employment status and health workers play a role in the declining utilization of antenatal care services, with employment status identified as the most dominant risk factor.